Prevalence of hepatitis B virus infection in pregnant women with and without HIV in Jos, Nigeria. (March 2021) - Magaji, Francis A.; Okolo, Mark O.; Yiltok, Esther S.; Golit, William; Anzaku, Stephen A.; Ogwuche, Jerry; Pam, Victor C.; Ocheke, Amaka N.; Musa, Jonah; Isichie, Christien; Imade, Godwin E.; Mutihir, Josiah T.; et al.
Highlights: Pregnant women living with HIV have higher prevalence of hepatitis B virus (HBV) than those without HIV. Pregnant women with higher parity were more likely to have hepatitis B virus infection. Pregnant women with no prior hepatitis B virus vaccination have greater risk for hepatitis B virus infection. Increased coverage of hepatitis B virus prevention services in areas with endemic HBV and improved integration with HIV prevention of mother-to-child transmission services could greatly decrease HBV transmission and prevalence. Abstract: Objective: To compare the prevalence of hepatitis B virus (HBV) in pregnant women with and without human immunodeficiency virus (HIV) in Jos, Nigeria. Methods: This comparative cross-sectional study of pregnant women was undertaken between 1 November 2017 and 30 April 2018. Informed consent was obtained, demographic data and predictors for HBV were collected, and all women were screened for HIV and HBV. Descriptive statistics and multivariate analyses using STATA Version 15 were performed. Results: Of 3238 women enrolled, 12.6% and 7.2% of those with and without HIV had HBV, respectively ( P = 0.01). Women with HIV, higher parity [adjusted odds ratio (aOR) 0.68, P < 0.01], lower gestational age (aOR 1.04, P < 0.01) and without prior HBV vaccination (aOR 0.40, P < 0.01) were significantly more likely to have HBV infection. Conclusions: Among pregnant women, the prevalence of HBV was higher among those with HIV. Predictors of HBV included being multigravida or grand-multigravida, registration for antenatal care before 20 weeks of gestation, and no prior HBV vaccination. In settings with endemic HBV and HIV, integration of effective HBV and HIV prevention services could greatly decrease the transmission and prevalence of HBV.